Effect of Levothyroxine Sodium Tablets on Pregnancy Outcome and Offspring Development Quotient of SCH during Pregnancy. (28th March 2022) - Qian, Xiaoling; Sun, Yunying; Xu, Xiaohua
Abstract : Objective . To investigate the effect of levothyroxine sodium tablets (L-T4) on pregnancy outcome and offspring development quotient in patients with subclinical hypothyroidism (SCH) during pregnancy. Material and Methods. Pregnant women with gestational age less than 12 weeks who underwent the first prenatal examination in our hospital from January 2019 to December 2019 were prospectively selected as subjects. According to the level of thyroid hormone in pregnant women, they were divided into the treatment group (n = 63) and received L-T4 treatment, untreated group (n = 64), and control group (n = 54). Three groups of pregnancy outcomes, children's physical development, and the development of offspring were compared at when one full year of life. Results . After treatment, the contrast difference of the three groups about abortion and gestational diabetes mellitus (GDM) was statistically significant (P < 0.05 ). The abortion rate and gestational diabetes mellitus (GDM) in the untreated group were higher than those in the control group (P < 0.05 ). The contrast difference of the treatment group and control group about abortion and gestational diabetes mellitus (GDM) is not statistically significant (P > 0.05 ); The contrast difference of the three groups about a filial generation at birth and one-year-old body length is not statistically significant (P > 0.05 ). The contrast difference between the three groups of individual children who are one-year old having the individual action energy, material ability, speech ability, and human ability is statistically significant (P < 0.05 ). One-year-old developmental quotient (DQ) of the treatment group and control group was higher than that of the untreated group (P < 0.05 ); the Pearson correlation analysis showed that the treatment group TSH levels have no correlation between the offspring developmental quotient (DQ) level of one-year-old children (P > 0.05 ). Conclusion . Levothyroxine sodium tablets (L-T4) can not only improve the pregnancy outcome of patients with SCH during pregnancy but also play a positive role in improving the neurointellectual development of their offspring.